TEKNOLOGI AUGMENTED REALITY - Joefrie, Yuri Yudhaswana; Anshori, Yusuf (MEKTEK, 2011)
This journal delivers topic about augmented reality, which is technology that support combination betweenreal world and augmented world. Using webcam to capture the real word and processed usingARToolkitPlus library and the result is generated to the screen.